Effect of body mass index (bmi) on mortality and readmission of heart failure patients in cardiovascular outpatient care unit at dr. Soetomo hospital, surabaya - Lestari, Sella Rizkita; Andrianto, Andrianto; Nugroho, J (Folia Medica Indonesiana, 2017)
Obesity is one of risk factors for heart failure in both men and women. Paradoxically, recent studies have shown that high BMIs in heart failure patients were asssociated with better outcomes. This study was aimed to prove the effect of body mass index on mortality and readmission in heart failure patients in cardiovascular outpatient care unit at Dr. Soetomo Surabaya Hospital. The research design was observational analytical study. Subjects consisted of all patients with heart disease in cardiovascular outpatient care unit at Dr. Soetomo Surabaya Hospital that meet the inclusion and exclusion criteria. Through the purposive sampling, 59 patients diagnosed with heart failure were selected. Direct measurements of body weight and height were conducted in February through March 2014 to calculate the BMIs. Based on their BMIs, subjects were then placed into two categories, which were patients with normal and elevated BMIs. Information on deaths and readmissions were gathered in October 2014. The relationship between two variables were then analyzed using Fisher Exact Test. After 8 months of follow up, 5 people (8.5%) died of cardiovascular cause and 7 (11.9%) were re-admitted to the hospital. Among 28 patients with normal BMIs, 3 (10.7%) died and 3 (10.7%) were re-admitted. Among 31 patients with elevated BMIs, 2 (6.5%) died and 4 (12.9%) were re-admitted to the hospital. By using Fisher Exact Test, it was shown that there is no effect of BMI on mortality (p=0.661) and readmission (p=1.000) in heart failure patients.